2018
DOI: 10.1111/psyp.13279
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough percepts of famous faces

Abstract: Recently, we showed that presenting salient names (i.e., a participant's first name) on the fringe of awareness (in rapid serial visual presentation, RSVP) breaks through into awareness, resulting in the generation of a P3, which (if concealed information is presented) could be used to differentiate between deceivers and nondeceivers. The aim of the present study was to explore whether face stimuli can be used in an ERPbased RSVP paradigm to infer recognition of broadly familiar faces. To do this, we explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 34 publications
4
21
0
Order By: Relevance
“…The probes were presented infrequently, one in eight like in a lineup, which is rarer than the typical P300 CIT of 1 in 6 23 and was made possible due to the high speed of presentation (1 Hz without pauses). Fringe of awareness presentation This is similar to previous studies of Bowman et al 18 , 46 , 47 . We presented all stimuli on the fringe of awareness using backward masking with a very short (10 ms) stimulus-of-interest presentation, followed (60 ms gap) by two successive masks (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The probes were presented infrequently, one in eight like in a lineup, which is rarer than the typical P300 CIT of 1 in 6 23 and was made possible due to the high speed of presentation (1 Hz without pauses). Fringe of awareness presentation This is similar to previous studies of Bowman et al 18 , 46 , 47 . We presented all stimuli on the fringe of awareness using backward masking with a very short (10 ms) stimulus-of-interest presentation, followed (60 ms gap) by two successive masks (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The use of masking followed a previous attempt to detect face familiarity without masking, which did not show good results 2 , and another partly unsuccessful attempt to use RSVP (as in 18 , but using OMI and not P3 ERP). Bowman et al 46 have recently shown that famous (familiar) faces, but not novel (unfamiliar) faces break into awareness in RSVP, resulting in large differences between brain responses to the familiar and unfamiliar. We believe that the same principle works in our case, with the familiar stimuli (the reference, as well as the probes) but not the unfamiliar tending to break into awareness through the masks, resulting in an amplified difference and a sensitive method to dissociate between them.…”
Section: Discussionmentioning
confidence: 99%
“…Under a Global Neuronal Workspace interpretation, this later component could be considered to reflect the breakthrough of a stimulus representation into conscious experience ( Alsufyani et al 2019 ). While we did observe weak evidence of recollection of mismatched targets ( P = 0.020; BF10 = 2.720), indicating that mismatched targets were not entirely unintelligible perhaps due to a degree of perceptual learning across the experiment ( Hervais-Adelman et al 2008 ), attentive participants’ ratings of intelligibility (noisiness) were entirely consistent with the pop-out of meaning following matched primes ( Davis et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under a Global Neuronal Workspace interpretation, this later component could be considered to reflect the breakthrough of a stimulus representation into conscious experience (Alsufyani et al, 2019). While we did observe weak evidence of recollection of mismatched targets (p=.020; BF10 = 2.720), indicating that mismatched targets were not entirely unintelligible perhaps due to a degree of perceptual learning across the experiment (Hervais-Adelman et al, 2008), attentive participants' ratings of intelligibility (noisiness) were entirely consistent with the pop-out of meaning following matched primes (Davis et al, 2005).…”
Section: Histogram Shows the Distribution Of Bayes Factors Across Thementioning
confidence: 99%